THE ROLE OF CULTURAL FACTORS AND TRENDS IN THE DEVELOPMENT OF LANGUAGES (World Bulletin of Management and Law, 2025)
The present article is devoted to the study of the coverage in scientific literature of one of the most pressing problems of linguistics – the role and significance of the principle of historicity in linguistic research. Naturally, this includes such issues as the nature, types and scale of changes in language, as well as the impact of these changes on the expansion or narrowing of the functional aspects of language. The article shows the reasons for these negative trends observed in the history of linguistics, the main manifestations of anthropocentrism, as well as how failure to comply with the principle of historicity in the study of languages, errors in the application of its principles and insufficient understanding of it can hinder the correct assessment of the essence and patterns of language development.
Keywords: Principle of historicizm; historical category; ethnogenetic research